Vertical profiles of tropospheric ozone from MAX-DOAS measurements during the CINDI-2 campaign: Part 1 - development of a new retrieval algorithm - Wang, Yang; Lampel, Johannes; Platt, Ulrich; Schmitt, Stefan (Journal of geophysical research. Atmospheres, 2018)
Ground-based measurements of tropospheric ozone (O3) are valuable for studies of atmospheric chemistry, air pollution, climate change, and for satellite validation. The Multi Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) technique has been widely used to derive vertical profiles of trace gases and aerosols in the troposphere. However, tropospheric O3 has not yet been satisfactorily derived from MAX-DOAS measurements due to the influence of stratospheric O3 absorption. In this study, we developed two new retrieval approaches for tropospheric O3 from MAX-DOAS measurements. In method 1, stratospheric O3 profiles from external data sources are considered in the retrieval. In method 2, stratospheric and tropospheric O3 are separated based on the temperature-dependent differences between tropospheric and stratospheric O3 absorption structures in the UV spectral range. The feasibility of both methods is first verified by applying them to synthetic spectra. Then they are applied to real MAX-DOAS measurements recorded during the CINDI-2 campaign in Cabauw, the Netherlands (September 2016). The obtained results are compared with independent O3 measurements and global chemical transport model simulations. Good agreement of the near-surface O3 concentrations with the independent data sets is found for both methods. However, tropospheric O3 profiles are only reasonably derived using method 1, while they are significantly overestimated at altitudes above 1 km using method 2, probably due to the approximation of the ring spectra used to correct the rotational Raman scattering structures in the DOAS fit. Advantages and disadvantages of both methods are discussed and improvement directions are suggested for further studies.